Perencanaan Perawatan dan Perbaikan Mesin Parut Kelapa Kapasitas 15 kg/Jam dengan Metode IRRO - Rismansyah Rismansyah; Syamsul Hadi; Muhammad Fauzan Hidayatu Ar Rijal; Venus Linggar Pribumi; Wildhan Hidayatullah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The problem with the coconut grater machine is that the machine has decreased performance after being used for several years, especially in the mechanical components (electric motor, V belt, Pulley, grater knife, hopper) and its electricity. The purpose of maintenance and repair planning is to obtain costs, maintenance and repair schedules for the period 2026, and the ratio of maintenance costs to profit. The maintenance and repair planning method includes collecting previous maintenance data, applying the inspection-replace-repair-overhaul (IRRO) method, evaluating component conditions, predicting component lifespan, predicting labor costs, predicting supporting equipment that will be used in maintenance, predicting the time to replace spare parts or reinstall repaired components, estimating maintenance and repair costs for the 2026 period, and calculating the maintenance cost to profit ratio. The results of maintenance and repair planning obtained maintenance costs for the 2026 period were IDR 957,000 with an estimated coconut grater machine rental rate of IDR 10,000/hour which has the potential to be rented for 900 hours/year, and the maintenance cost to profit ratio was 10.6% which implies that the coconut grater machine with a capacity of 15 kg/hour is still prospective and feasible to use for the next few years.